Positive Solution of a Nonlinear Fractional Differential Equation Involving Caputo Derivative - Changyou Wang; Haiqiang Zhang; Shu Wang (Discrete Dynamics in Nature and Society)
This paper is concerned with a nonlinear fractional differential equation involving Caputo derivative. By constructing the upper and lower control functions of the nonlinear term without any monotone requirement and applying the method of upper and lower solutions and the Schauder fixed point theorem, the existence and uniqueness of positive solution for the initial value problem are investigated. Moreover, the existence of maximal and minimal solutions is also obtained.